2012
DOI: 10.1155/2012/641087
|View full text |Cite
|
Sign up to set email alerts
|

PPAR and Oxidative Stress: Con() Catenating NRF2 and FOXO

Abstract: Peroxisome-proliferator activator receptor γ (PPARγ) is a nuclear receptor of central importance in energy homeostasis and inflammation. Recent experimental pieces of evidence demonstrate that PPARγ is implicated in the oxidative stress response, an imbalance between antithetic prooxidation and antioxidation forces that may lead the cell to apoptotic or necrotic death. In this delicate and intricate game of equilibrium, PPARγ stands out as a central player devoted to the quenching and containment of the damage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
180
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 205 publications
(183 citation statements)
references
References 154 publications
(242 reference statements)
3
180
0
Order By: Relevance
“…This suggested that a positive feedback loop exists between PPARγ and Nrf2. 21 Interestingly, 15d-PGJ 2 rapidly activates Nrf2 in cardiomyocytes, whereas PGD 2 -FP receptor signaling activates Nrf2 more slowly (although an FP receptor agonist increased the mRNA expression of Nrf2 target genes from 12 hours after treatment, whereas the same effect started at 3 hours and peaked at 6 hours after the addition of 15d-PGJ 2 ). On the basis of these observations, we conclude that 15d-PGJ 2 and PGD 2 -FP receptor signaling eventually converge to activate the transcription factor Nrf2 and that the different dynamics of Nrf2 activation via these 2 signaling pathways contribute to the sustained activation of Nrf2 in the heart after DEX treatment ( Figure S6).…”
Section: Discussionmentioning
confidence: 97%
“…This suggested that a positive feedback loop exists between PPARγ and Nrf2. 21 Interestingly, 15d-PGJ 2 rapidly activates Nrf2 in cardiomyocytes, whereas PGD 2 -FP receptor signaling activates Nrf2 more slowly (although an FP receptor agonist increased the mRNA expression of Nrf2 target genes from 12 hours after treatment, whereas the same effect started at 3 hours and peaked at 6 hours after the addition of 15d-PGJ 2 ). On the basis of these observations, we conclude that 15d-PGJ 2 and PGD 2 -FP receptor signaling eventually converge to activate the transcription factor Nrf2 and that the different dynamics of Nrf2 activation via these 2 signaling pathways contribute to the sustained activation of Nrf2 in the heart after DEX treatment ( Figure S6).…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, knockdown of PPAR-γ reduced the mRNA expression for Nrf2. This indicates a tight, positive, two-way reinforcing transcriptional interaction between PPAR-γ and Nrf2 that may improve endothelial function [31]. …”
Section: Discussionmentioning
confidence: 99%
“…It is also important for the regulation of insulin-stimulated metabolic pathways in human adipocytes (24). Furthermore, it has been reported that phosphorylation of Akt reduces the expression of forkhead transcriptional factor 1 (Foxo1), which is an antagonist of PPAR-γ, thus enhancing the expression of PPAR-γ indirectly and promoting adipogenesis (25,26). In addition, Akt phosphorylation activates C/EBPα during preadipocyte differentiation (21).…”
Section: Discussionmentioning
confidence: 99%